Effect of subsurface voids on the nanoindentation of Fe crystals - Hofer, Juan Andres (2020)
Subsurface voids may strongly affect the response of materials to nanoindentation. We explore these effects for a bcc single-crystalline Fe sample using molecular dynamics simulation. Deformation occurs mainly by nucleation and propagation of dislocations. As dislocations impinge into the voids, these suffer a reduction in volume, consistent with mass transfer mechanisms. Our results show that voids act as highly efficient absorbers of dislocations, effectively limiting the extension of the plastic zone. Surprisingly, mechanical properties are marginally affected by the presence of voids in the range of sizes and spatial distributions tested, except for voids a few nanometers below the surface. Deformation twinning is observed as a transient effect in some cases; however, for voids close enough to the indentation area, no twinning was found.